(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract This paper explores the role of digital technologies in fostering creative competence in biochemistry education. As biochemistry is a field that demands both technical knowledge and innovative problem-solving skills, creative competence is essential for students preparing for careers in medical and scientific fields. Digital technologies, including virtual labs, biochemical modeling software, and interactive simulations, provide versatile, scalable tools that enhance active learning, improve comprehension of complex concepts, and enable students to engage in innovative applications of biochemistry. This paper reviews various methodological approaches to integrating these technologies effectively and discusses their implications for biochemistry education.